Implementasi Elliptic Curve Digital Signature Algorithm Untuk Smart Gerobak Sorong Dalam Monitoring Pakan Ternak - Alvi Suhartanto; Heni Sulistiani; Selamet Samsugi; Reflan Nuari; Izudin Ismail (LPPM STIKI MALANG, 2024)
The Internet of Things (IoT) implementation in the livestock sector includes the use of sensors, software and internet-based platforms to monitor, manage and optimize in real-time. This research is intended to solve problems at PT. Indo Prima Beef noted that the use of animal feed is still based on estimates, resulting in the calculation of the selling price of cattle being inaccurate and potentially detrimental. Manual recording which is prone to errors and less efficient causes uncertainty in feed management and costs. Therefore, this research develops an IoT-based tool that is integrated in a wheelbarrow. This tool is capable of reading the results of weighing animal feed and storing the data in real-time in a database connected to web monitoring. Apart from that, the monitoring application can display recap results of cow feed weights, there are also features that support optimal use of the Smart Gerobak Sorong. The method used in this research is applying the Elliptic Curve Digital Signature Algorithm as a safeguard for data communication between IoT and the database. Based on the test results on a cow's feed weight of 10.6 kg, a difference value of 0.11 kg was obtained. This means that the average error value is 0.01%. So, it can be concluded that the loadcell sensor can read mass data for weighing cattle feed with the same load. With this tool, PT. Indo Prima Beef can increase the efficiency of feed use, optimize business income, and provide innovative and effective solutions in overall animal feed management.